Simulation on pyrolysis behavior and reaction pathway of natural rubber and styrene-butadiene rubber by ReaxFF-MD - Xiaohua Li; Weiming Liu; Junlong Wang; Shanshan Shao; Weiliang Ding (eXPRESS Polymer Letters)
Pyrolysis is one of the effective methods for recycling waste tire rubber, and there are fewer studies on the simulation and mechanism of pyrolysis of multi-component mixed rubber. This study employs reactive force field molecular dynamics (ReaxFF-MD) simulations to analyze the pyrolysis product evolution processes of natural rubber (NR), styrene-butadiene rubber (SBR), and mixed rubber (NR/SBR). The results show that with increasing temperature, the gas yield of NR/SBR increases from 16.32% at 2000 K to 37.01% at 3000 K, and the molecular numbers of gas products such as H2 and small-molecule hydrocarbons increase with temperature. The co-pyrolysis of NR/SBR accelerates solid rubber pyrolysis time and promotes the formation of main gas products (excluding C4H6). Using simulation results, the reaction pathways of pyrolysis intermediates were analyzed: the main intermediates of NR are isoprene monomers and C10H16• short-chain radicals, while those of SBR are styrene and butadiene. The bond cleavage mechanisms of intermediates were compared through reaction energy barrier calculations. This study systematically reveals the pyrolysis product characteristics and reaction mechanisms of rubbers, providing theoretical support for the selective pyrolysis recycling of various waste rubbers.